Genetic variability in wood apple (Feronia limonia) from Gujarat - SINGH, A K; SINGH, SANJAY; YADAV, VIKAS; SHARMA, B D (The Indian Journal of Agricultural Sciences, 2016)
Considering the wide genetic diversity in wood apple (Feronia limonia) in terms of fruit shape, size, colour and qualitative characters, an extensive survey of diversity rich area of Gujarat was made and twenty five genotypes in the form of fruits were collected from the different locations during 2015-16 to identify elite genotypes having desirable horticultural traits. All the existing trees are of seedling origin which offer a great scope for selection of suitable genotypes of high yield potentiality with good fruit quality traits having precocity in bearing, less spine intensity and other desirable characters. Variations in morphological characters were noticed in the naturally grown trees at their locations, whereas chemical analysis was done in laboratory of the station. Fruits of genotype, viz. GW-1, GW-4, GW-12, GW-14, GW-16, GW-18, Gw-20 and GW-24 were observed to be round, whereas flattened round in GW-2, GW-5, GW-6, GW-8, GW-9, GW-10, GW-13, GW-17, GW-21and GW-23; triangular in GW-7 and GW-11, and oblong in GW-3, GW-15, GW-19, GW-22 and GW-25 fruit shape was observed. Physico-chemical analysis of fruits divulged that the fruit weight ranged between 156.45-432.93g, while fruit length and width between 5.25-9.46 cm and 5.10-9.29 cm, respectively. Shell thickness, shell weight, pulp weight, number of seeds per fruit and seed weight per fruit ranged between 0.31 to 0.47cm, 67.94-109.77g, 80.04 to 319.32g, 132.34 to 525.81 and 2.36 to 7.93g, respectively. Results of study revealed that the different genotypes exhibited wide range of variability in qualitativecharacters, viz. total soluble solids (11.07-19.36 0Brix), acidity (3.23-6.86%), ascorbic acid (7.08-19.60mg/ per100 g), potassium (1.29-1.86%), phosphorus (0.037- 0.078%), calcium (0.11- 0.39%), magnesium (3.18-5.92 %), sodium (3.07-7.54%) and pectin content (1.39-1.65%), among all the genotypes studied for their qualitative characters.